Parenting stress among parents of children with attention-deficit/hyperactivity disorder, the role of control and responsibility attributions - Bromley Little, Heather Joya (University of Waterloo, 1998)
Studies of the predictors of parenting stress have tended to neglect the role of parental cognitions. Two studies were conducted to examine the contribution of parents' self- and child-focused attributions of control and responsibility to parenting stress among parents of children displaying various degrees of Attention-Deficit/Hyperactivity Disorder (ADHD) behaviours. As a secondary focus, differences in parental adjustment difficulties were investigated among parents whose children evidenced low or high levels of ADHD as well as Oppositional Defiant Disorder (ODD) symptomology. Study one involved a community sample of 234 parents (primarily mothers of boys with a pre-established ADHD diagnosis); study two's sample included 156 parents attending community support groups for parents of children with ADHD. Parent attributions were measured using an analogue method in which parents made ratings in response to various scenarios depicting typical child misbehaviours or poor parent-child interactions. Both studies supported the hypothesis that perceiving child misbehaviours as being beyond parental control predicted parenting stress even when child behaviour problems, parental depressed mood, family dysfunction (in study one) and child age (in study two) were statistically controlled. The second study, utilizing a comprehensive approach to the measurement of parental attributions, found that attributions of high child responsibility also contributed significant variance to parenting stress beyond the influence of several other variables. The subscales of a measure of causal control attributions (Parent Attribution Test), however, were not successful in predicting parenting stress. Across the parental adjustment indices within both studies, adjustment problems in parents were dependent upon children's levels of ADHD and ODD symptomatology. However, ODD behaviours played a more significant role in parental depressed mood than did ADHD behaviours, and some evidence for the greater importance of ODD symptomatology in family dysfunction was found. For the parenting stress variable, the following pattern resulted: parents of nonproblem children reported the lowest stress, the combined ADHD and ODD group showed the worst, and the pure ADHD and pure ODD groups fell in the midrange. The results suggest the need for more comprehensive assessment of families with children displaying ADHD symptomatology, and the inclusion and empirical evaluation of attributional training segments in parenting programs.
Keywords: Harvested from Collections Canada